Maximal cardiorespiratory responses of adolescent athletes to treadmill running and arm ergometry: Swimmers vs soccer players - Al-Hazzaa, H. M.; Al-Refaee, S. A.; Sulaiman, M. A.; Al-Herbish, A. S.; Chukwuemeka, A. C. (Medicine & Science in Sports & Exercise, 1996)
Adolescent male swimmers and soccer players performed on a running treadmill and arm ergometer. VO2max was measured during each activity. It was found that soccer players recorded significantly higher VO2max values than swimmers in the more soccer-related activity of treadmill running. During arm ergometry, swimmers produced higher VO2max values which, however, were not significantly different. The closer scores in the arm activity suggests that total body activities (e.g., running, rowing, cross-country skiing) might produce more discriminable adaptations of a physiological nature than do less-than-total-body activities (e.g., cycling, swimming) even though the degree of specific-activity adaptation is the same in both activities. Implication. This study supports the specificity of adaptation that results from training. It is recommended that only activity-specific ergometry be used when assessing physiological training responses. The specificity of training was demonstrated in male adolescent athletes.